ENT530 : Peanutlicious Bakery and Cafe / Muhammad Adlan Abdul Jamil ... [et al.] - Abdul Jamil, Muhammad Adlan; Rosnan, Muhammad Izzat; Abu Samat, Noor Syahirah; Shahrul Zahri, Muhammad Nor Azizi; Zamrin, Nur Azryna (2019)
Peanutlicious Bakery and Cafe have been recognized by among the sacred people of Keramat Kuala Lumpur, Peanutlicious bakery and cafe has started its business since 2016. Peanutlicious bakery and cafe provides various bakery of food products to the public, the main product is birthday cake. In addition, Peanutlicious Bakery and Cafe also produces cupcake products and brownies. The company also receives cake orders from customers and provides cake delivery services to customers. Peanutlicious Bakery and Cafe started from home bakery before their expend business to open shop at Ampang Selangor.